Verasitas Versus Viralitas: Refleksi Filosofis atas Karya-Karya Bandung Photography Triennale 2022 - Mardohar Batu Bornok Simanjuntak; Henrycus Napitsunargo; Deden Hendan Durahman (Universitas Katolik Parahyangan, 2022)
The reality of our everyday life is now stifled by dense images taken by mobile phones. It is still acceptable to claim that digital photographic images are currently invading the phone memory space and social media communication platforms used for working and daily activities like Whatsapp, Instagram, or Telegram. The sheer production and distribution of such images give rise to the virality of malicious digital photographs. This unfortunate circumstance can lead to the negative spread of hoaxes, misinformation, and disinformation. Virality then undermines veracity. Digital photographic records fabricated exponentially are then thinning the line between the truth and the viral. Such image manipulation is indeed a serious problem because public scamming is now orchestrated and conducted through digitally reconstructed images which are aggressively invading chatrooms. To cope with this surge, the authors propose philosophical analyses through examining all possible ways to manipulate photographic images conceived by 35 artists participating in Bandung Photography Triennale 2022. As analytical instruments to probe the prospect of veracity to distance itself from virality, the authors employed three triangulated categories extracted from philosophical discourses on photography, that is, the Eye, the time signature, and the ideology.